DEVELOPMENT STUDENT WORKSHEET ASSISTED WITH NUMBERED HEAD TOGETHER MODEL RELATED TO MATHEMATICS PROBLEM SOLVING ABILITY - Eko Edi Sujarwo; Sugeng Sutiarso (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
The capacity to fathom scientific issues can offer assistance a understudy unravel a mathematical issue inside the scope of learning conjointly in existence . Powerless issue understanding capacities experienced by students can result in not accomplishing the objectives of learning results within the learning process. This investigate itself has the objective of creating a LKPD learning apparatus utilizing the Numbered Head Together show which is anticipated to make strides students' mathematical issue tackling capacities, with substantial and down to earth categories. The type of research conducted was Research and Development, with 24 class VIII students as research subjects. The information analysis strategy utilized is legitimacy and common sense investigation. Information collection methods are interviews, surveys, and tests. Information analysis methods in this consider included preparatory information examination, information validity investigation by specialists, and information common sense examination by instructors and students. From the comes about of this think about, it was concluded that the advancement of LKPD learning instruments with the assistance of the Numbered Head Together show to move forward students' mathematical issue tackling capacities based on master validators, teachers, and students in meeting the criteria of validity and practicality. Kemampuan pemecahan pada masalah matematika bisa membantu seorang siswa dalam memcahkan suatu permasalahan matematika didalam ruang lingkup pembelajaran dan juga didalam kehidupan sehari-hari. Lemahnya kemampuan pemecahan masalah yang dialami siswa bisa mengakibatkan tidak tercapainya tujuan dari hasil belajar pada proses pembelajaran. Penelitian ini sendiri mempunyai tujuan menghasilkan suatu perangkat pembelajaran LKPD dengan menggunakan model Numbered Head Together diharapkan dapat meningkatkan kemampuan pemecahan matematika siswa, dengan kategori yang relevan dan praktis. Jenis penelitian yang dilakukan adalah Research and Development, dengan subjek penelitian sebanyak 24 orang siswa pada kelas VIII. Teknik analisis data yang digunakan adalah analisis validitas dan analisis kepraktisan. Teknik pengumpulan data adalah wawancara, angket dan tes. Teknik analisis data dalam penelitian ini meliputi analisis data pendahuluan, analisis validitas data oleh ahli, dan analisis kepraktisan data oleh guru dan siswa. Berdasarkan hasil penelitian dapat disimpulkan bahwa pengembangan perangkat pembelajaran LKPD dengan model Numbered Head Together untuk meningkatkan kemampuan pemecahan masalah matematika siswa berdasarkan validator ahli, guru dan siswa yang memenuhi kriteria kevalidan serta kepraktisan.